Indução de resistência por Bacillus amyloliquefaciens e Lactobacillus paracasei à Phytophthora nicotianae em porta-enxertos de citros - Costa, Wesley Luiz Fialho (2017)
Citriculture is one of the most important crops influencing the agricultural trade balance. It is estimated that half of the orange juice consumed in the world is produced in Brazilian orchards. In the last years the citriculture has been suffering from many risk factors, such as high incidence of pests and diseases. The introduction of Huanglongbing in Brazil raised the costs of spraying in the last years, besides leading to the eradication of several citrus trees. Thus, the replacement of these threes has made seedlings the main input in citriculture. In nursery seedlings, Phytophthora spp. Pathogens that causes citrus gummy are of great importance, but difficult to control because there are few effective active ingredients. The biological control has been showing good results in controlling these diseases using antagonistic bacteria, although stills incipient. Thus, the aim of this study was to evaluate the ability of the two bacterial isolates Lactobacillus paracasei and Bacillus amyloliquefaciens in inducing the production of phenolic compounds and activating defense enzymes of two citrus rootstocks Phytophthora nicotianae. Seeds of Citrus sunki and Poncirus trifoliata, susceptible and resistant to P. nicotianae, respectively, were microbiolized with the bacteria in three assays. The substrate was inoculated with the phytopathogen at 75 days after sowing (assay 2), and the lap region was inoculated at 90 days after sowing (assay 3). The plant shoot was used to quantify the enzymes polyphenoxidase (PPO), peroxidase (POD), phenylalanine ammonia-lyase (PAL) and phenolic compounds. P. sunki plants non-inoculated with P. nicotianae (assay 1) showed higher levels of enzymatic activity of all enzymes, except POD, and plants inoculated with B. v amyloliquefaciens presented high activity of PAL and PPO. Plants inoculated with L. paracasei showed higher concentration of phenolic compounds. All C. sunki grown in substrate inoculated with P. nicotianae presented an increased in the enzymatic activity. PPO and PAL showed higher level of activity in the treatments with the bacteria, and there was accumulation of phenolic compounds. In P. trifoliata there was high activity of POD in plants treated with B. amyloliquefaciens. High activity if PAL was observed after inoculation by P. nicotianae in all treatments. C. sunki plants inoculated in lap region (assay 3) showed higher severity, and presented higher activity of POD and concentration of phenolic compounds when treated with B. amyloliquefaciens. In conclusion, L. paracasei and B. amyloliquefaciens activated the defense system of citrus plants, however the enzymatic activity depends on the variety of the rootstock and if the plants were inoculated with the phytopathogen.